Fracture Resistance and Failure Modes of Endodontically Treated Molars Restored by Endocrowns Made of Glass Ceramic or Indirect Composite Resin (an in-vitro study) - جاموس عصام; غلاونجي ياسمين (Latakia University Journal -Medical Sciences Series, 2020)
Objective: The aim of this study was to evaluate the fracture resistance of molars restored with endocrowns made of glass-ceramic (LDS) and indirect composite. Materials and Methods: 36 extracted molars were divided into three groups. Teeth in group1 (intact) were left without treatment. Remaining teeth were sectioned 2mm above CEJ and undergone to standardized preparation. Endocrown restorations made of LDS were used for group2 (e-max), while indirect composite was used for group3 (composite). A compressive axial load was applied until failure. Fracture loads and failure modes were recorded. Statistically analysis was performed using one-way analysis of variance. Results: Mean fracture strength of group (e-max) was (4842 N) and showed significantly higher value than that of other two groups, whilst mean fracture loads of groups (composite) and (intact) did not show statistically differences (3016 and 2708 N respectively). All specimens of groups (e-max) and (composite) exhibited irreparable fractures, while failure modes of (intact) ranged between repairable and irreparable. Conclusion: Endocrowns made of indirect composite can be used to restore endodontically treated molars as they provide the ability to modify and repair if necessary.